PENGARUH KESADARAN LINGKUNGAN TERHADAP MINAT MAHASISWA DALAM PEMANFAATAN SUMBER DAYA ALAM BERKELANJUTAN - agustin, marshanda (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2025)
The purpose of this study was to explore the impact of environmental awareness on students' interest in utilizing natural resources sustainably. By applying quantitative research methods through a survey approach, data were obtained through electronic questionnaires distributed to 40 students of the Economics Education program at Medan State University. The results of a simple linear regression analysis showed that environmental awareness has a significant positive effect on students' interest, with the regression equation Y = -0.927 + 1.023X. Every one unit increase in environmental awareness will cause an increase in student interest by 1.023 units. The t-test results showed a significance value with a p of 0.000, resulting in the rejection of the null hypothesis. The adjusted R² analysis showed that 65.8% of the variation in student interest could be explained by environmental awareness, while 34.2% was influenced by other factors. These findings emphasize the importance of environmental education in shaping students' attitudes towards natural resource conservation. Therefore, increasing education and socialization regarding environmental issues is very much needed to encourage sustainable practices among students.